Health behaviors of patients with arterial hypertension aged 60-70 treated in the cardiology department - Ewelina Bąk; Jadwiga Piętka; Anna Pawlak (Journal of Education, Health and Sport, 2023)
Introduction and purpose of the study: Arterial hypertension is currently the biggest economic problem among cardiovascular diseases. It concerns the population of the elderly, in whom health behaviors are necessary, but difficult to implement. Hospitalization of such patients creates an opportunity for education and preventive actions in the field of proper health behavior.